MENINGKATKAN AKTIVITAS SISWA, MOTIVASI, KARAKTER WASAKA DAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DAN CHILDREN LEARNING IN SCIENCE PADA MUATAN IPA KELAS VB SDN BASIRIH 1 BANJARMASIN - Radiva Rahmi; Muhsinah Annisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem of this research is where during science learning students tend to be passive and do not want to ask questions when the teacher asks questions to students, they only answer these questions with answers that are already listed in the book. To follow up on these problems, the researchers tried to provide a solution to the problem, namely by using a combination of learning models consisting of Problem Based Learning (PBL), Children Learning In Science (CLIS). The approach used in this research is qualitative research and this type of research applies classroom action research. The types of data presented in this study are qualitative data and quantitative data. Qualitative data in the form of data on teacher activities, student activities and student learning motivation in teaching and learning process activities, through observation with observation sheets. Quantitative data in the form of student learning outcomes obtained through written tests at the end of each meeting. This research was conducted at SDN Basirih 1 Banjarmasin in the even semester of class VB in the 2023/2024 academic year. After conducting 4 meetings with 2 cycles, the results showed that the activities of teachers, students, student learning motivation, WASAKA character and learning outcomes increased in each cycle with the categories